(3efXheI GdCUagGfj aj GdbQGAGJs - (3WGgQ GdMGaX GdCUagGfjs ((3YHOGddg HjTGOhj s)
(3ChdgG (B:s
(3HMeO Edg GdNdb Pj GdaVd hGdGdG hTcQ CjGJg GaJJMJ eSedG dLCJ djg VGQYkG eJYhPkG Hg ef TQhQ GdfaS bhdkG heaYdkG s
(3BNQgG (B:s
(3hbO QMeJ HGdMeO hGdUdGI HYO Ydi NjQ GdhQi YWQ GdedG eMeO GdegOj hGdBd hUMHg hUdGI HgG fQLh GdTaGYI s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCRgQjI s
Keywords: (3GdbQGAGJ hGdJLhjOs